2019
DOI: 10.1016/j.jacr.2019.02.011
|View full text |Cite
|
Sign up to set email alerts
|

ACR Appropriateness Criteria® Clinically Suspected Adnexal Mass, No Acute Symptoms

Abstract: There are approximately 9.1 pelvic surgeries performed for every histologically confirmed adnexal malignancy in the United States, compared to 2.3 surgeries per malignancy (in oncology centers) and 5.9 surgeries per malignancy (in other centers) in Europe. An important prognostic factor in the long-term survival in patients with ovarian malignancy is the initial management by a gynecological oncologist. With high accuracy of imaging for adnexal mass characterization and consequent appropriate triage to subspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 56 publications
0
33
0
1
Order By: Relevance
“…The heterogeneous nature of mucinous carcinoma, often coexisting with benign and borderline mucinous elements, suggests that mucinous carcinoma develops in a stepwise fashion from and color or power Doppler techniques, as the imaging modality of choice in patients with signs and symptoms suggestive of an adnexal mass (26). US is useful in determining the anatomic origin of the adnexal mass.…”
Section: Mucinous Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…The heterogeneous nature of mucinous carcinoma, often coexisting with benign and borderline mucinous elements, suggests that mucinous carcinoma develops in a stepwise fashion from and color or power Doppler techniques, as the imaging modality of choice in patients with signs and symptoms suggestive of an adnexal mass (26). US is useful in determining the anatomic origin of the adnexal mass.…”
Section: Mucinous Carcinomamentioning
confidence: 99%
“…CT is not recommended in initial evaluation of a suspected adnexal mass (26). In the setting of an indeterminate complex cystic mass, CT may be useful in confirming the diagnosis of a mature cystic teratoma by demonstrating inter- nal macroscopic fat and coarse calcifications/ teeth (36).…”
Section: Detection and Characterizationmentioning
confidence: 99%
“…CA 125 results were limited and CA125, ROMA, and OVA-1 were not routinely ordered for the patients selected. Studies have demonstrated that a generalist's expertise in subjective assessment with ultrasound findings may offer a better "diagnostic certainty" in differentiating between benign and malignant masses compared to tumor markers and algorithms [2,[11][12][13]. Although tumor markers are widely used, many researchers have also proved that women with ovarian cancer can have a normal CA 125 level [2,5].…”
Section: Discussionmentioning
confidence: 99%
“…With the reliance of laboratory testing and imaging, as well as increasing obesity levels limiting pelvic exams, there is a declining trend of accurately diagnosing patients solely based on physical exams [7]. Despite technological developments in analyzing adnexal masses, studies have shown that subjective assessments performed by experienced physicians have high sensitivities and specificities and are superior to other available classification systems or algorithms [5,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Incidental adnexal masses are commonly detected in daily medical practice due to the frequent lack of clinical manifestation. 1 Approximately 9% to 10% of women undergoing ultrasound have ovarian lesions. 2 Although most commonly used, ultrasound has some limitations including the small field of view, low resolution and interference by obesity or by gaseous bowel loops.…”
Section: Introductionmentioning
confidence: 99%